Respostas

2014-03-13T11:57:09-03:00
A=1
b=-2
c=-7

x=-b +- raiz quadrada de (b^(2)-4.a.c/2.a

x=-(-2)+-raiz quadrada de (-2)^(2)-4.1.(-7)/2.1

x=2+-raiz de 4+28/2

X=2+- raiz de 32/2

só melhorando a resposta:

x'=2+ 4.raiz de2
              2

x''=2-4.raiz de 2
              2
 


2014-03-13T12:09:01-03:00
X²-2x-7=0                                                                             fatorar 32|2
Δ= b²-4ac                                                                                         16|2
                                                                                                           8|2
a=1                                                                                                     4|2
b=-2                                                                                                     2|2 
c=-                                                                                                                                                                                                                                                                                                                √ 2².2²2 = 2.2√2.
Δ=(-2)²-4(1)(-7)                                                                              4√2
Δ=4+28
Δ=32 se Δ>0 então x= -b+ -√Δ/2a
x'= -(-2)-√32/2(1)
x'=2-4√2/2
x'=1-2√2
e
x"=-(-2)+4√2/2
x"=2+4√2/2              x" 1+2√2